The contribution of cutaneous thermal signals to bodily self-awareness - Gerardo Salvato; Paul Mark Jenkinson; Manuela Sellitto; Damiano Crivelli; Francesco Crottini; Teresa Fazia; Silvia Amaryllis Claudia Squarza; Mariangela Piano; Maria Sessa; Martina Gandola; Aikaterini Fotopoulou; Gabriella Bottini (Nature Communications)
Abstract Thermosensory signals may contribute to the sense of body ownership, but their role remains highly debated. We test this assumption within the framework of pathological body ownership, hypothesising that skin temperature and thermoception differ between right-hemisphere stroke patients with and without Disturbed Sensation of Ownership (DSO) for the contralesional plegic upper limb. Patients with DSO exhibit lower basal hand temperatures bilaterally and impaired perception of cold and warm stimuli. Lesion mapping reveals associations in the right Rolandic Operculum and Insula, with these regions linked to lower skin temperature located posterior to those associated with thermoception deficits. Disconnections in bilateral parietal regions are associated with lower hand temperature, while disconnections in a right-lateralized thalamus-parietal hub correlate with thermoception deficits. We discuss the theoretical implications of these findings in the context of the ongoing debate on the role of homeostatic signals in shaping a coherent sense of body ownership.